Atrial Myxoma – A Rare Cause of Heart Failure - Oluwole G Adeoye; Rafiu Adefila; Maruf A Jimoh; Temitope Farayola; Jamiyu Lawal; Sumaila Ahmodu; James A Ogunmodede (International Journal of Medicine and Health Development)
Atrial myxomas are rare cardiac tumors that usually present with diverse, unrelated symptoms. Conversely, heart failure (HF) is a common cardiac disorder that is mostly caused by uncontrolled systemic hypertension. It is a progressive cardiac disease that is managed with guideline directed medical therapy (GDMT). We present the case of a farmer who presented with typical symptoms of HF. Echocardiography however revealed an unusual cause of his symptoms—a huge mass in his left atrium (LA) prolapsing through the mitral valve, causing functional mitral stenosis. The mass is suspected to be an atrial myxoma. Surgical excision of this mass is proposed as the cure, which will obviate the need for continuous use of GDMT. This case report and literature review bring to fore the mechanisms by which atrial myxoma can cause HF and the other varied clinical presentations of atrial myxomas.